Blood biomarkers for estimating energy intake in Japanese male collegiate athletes: a pilot study - Yuka Kurosaka; Takaaki Nagasawa; Kumiko Minato; Tomomi Hasegawa-Tanaka; Hisashi Naito; Sawako Wakui; Shuichi Machida (BMC, 2023)
Abstract Background Athletes should be informed of their required energy intake in preparation for sports competitions. However, the environment in which dietary surveys can be conducted to determine the required energy intake for sports competitions is limited, and such survey will require a substantial amount of time and effort from athletes and dietitians. If certain biomarkers for estimating the energy intake can be identified, they may compensate for the shortcomings of these dietary surveys. We aimed to identify the blood biomarkers to estimate the energy intake/basal metabolic rate ratio of male athletes. Methods Twenty-six male athletes from a university physical education department were included and underwent measurements of height, weight, and body composition, as well as blood sampling. The dietary assessment included a 3-day dietary recall and collection of meal photographs. The basal metabolic rate was estimated using the lean body mass, while the daily energy intake/basal metabolic rate ratio was used as an index to determine the energy intake. From the 36 selected blood biomarkers, we identified the independent biomarkers for inclusion in the multiple regression analysis by assessing for pairwise correlations and multicollinearity. A formula for estimating the energy intake/basal metabolic rate was then developed using the stepwise method. A p-value of < 0.05 was considered significant. Results Overall, 18 of the 36 blood biomarkers were selected, and multiple regression analysis revealed that triiodothyronine, white blood cell count, and triglyceride level were significant factors that can be used to estimate the energy intake/basal metabolic rate, accounting for 60.4% of the variance. No systematic errors were observed in the estimated values, calculated using the estimation formula and dietary assessment results. Conclusions A combination of free triiodothyronine level, white blood cell count, and triglyceride level can be used for estimating the energy intake/basal metabolic rate of male athletes, thus compensating for the shortcomings of dietary surveys.